The Quality of Educational Services for Internship and Apprenticeship Courses at the Community Medicine Department of Kerman University of Medical Sciences, from the Trainees' View Point - Akram Karbakhsh; Ali Khalooei (Kerman University of Medical Sciences, 2018)
Background Community medicine departments play a major role in the education of medical students in order to provide primary health care services. The appropriate quality of education in such departments plays an important role in providing effective services for health promotion of communities. Objectives The current study was aimed to evaluate the quality of educational services at the Community Medicine Department of Kerman University of Medical Sciences from the viewpoint of interns and apprentices. Methods The current cross sectional, descriptive-analytical study was conducted on all medical students that completed their internship or apprenticeship course at the Community Medicine Department of Kerman University of Medical Sciences in 2016 as the study population. Data were collected by the service quality measurement questionnaire (SERVQUAL), and analyzed by Independent test, paired test, and one sample test, as well as Pearson correlation coefficient. Results Of 244 participants in the study, 58.2% (n = 142) were female and 41.8% (n = 102) male, 57% (n = 139) were in the internship and 43% (105) in the apprenticeship courses. From the students' point of view, the mean score of perception in all five dimensions of educational quality was significantly lower than the expectations score, which indicated a negative gap in the quality of educational services in all dimensions (P < 0.001). The greatest quality gap was observed in the responsiveness dimension (- 0.86) and the lowest in the assurance dimension (- 0.59). The utility level of the quality of educational services in the Department of Community Medicine was 84% from the viewpoint of the students. The highest level of utility in the quality of medical services was respectively observed in the dimensions of assurance (86.4%) and empathy (86.1%) and the lowest in responsiveness dimension (79.6%) (P < 0.001). The lowest and highest correlations were respectively observed between tangibles and assurance (r = 0.486) and between empathy and assurance (r = 0.708) dimensions. Conclusions In all five dimensions of the quality of educational services, there were negative gap that required planning for quality improvement. Issues such as modifying educational contents and tailoring training to future jobs, modifying educational methods, increasing the contribution of students to educational planning, and updating educational facilities should be considered more urgently in the education quality promotion programs.